The role of collisions on mode competition between the two-stream and Weibel instabilities - Humphrey, K; Trines, R; Speirs, D; Norreys, P; Bingham, R (2013)
We present results from numerical simulations conducted to investigate a potential method for realizing the required fusion fuel heating in the fast ignition scheme to achieving inertial confinement fusion. A comparison will be made between collisionless and collisional particle-in-cell simulations of the relaxation of a non-thermal electron beam through the two-stream instability. The results presented demonstrate energy transfer to the plasma ion population from the laser-driven electron beam via the nonlinear wave-wave interaction associated with the two-stream instability. Evidence will also be provided for the effects of preferential damping of competing instabilities such as the Weibel mode found to be detrimental to the ion heating process. © Cambridge University Press 2013.